Socio-demographic Status & Associated Risk Factors of the Stroke Patient's in a Tertiary Care Hospital of Bangladesh - Siddiqui, Mahmudur Rahman; Islam, Quazi Tarikul; Iqbal, Md. Jabed; Binte-Mosharraf, Sumaiya Sultana (Anwer Khan Modern Medical College Journal, 2013)
Stroke is the most common neurological emergency. A total number of 100 randomly selected, clinically and CT proven acute stroke patients were studied at medicine units of Dhaka Medical College Hospital. Socio-demographic data and major risk factors or co-morbid conditions among acute stroke patient were identified and correlated. Out of 100 patients 29% were in between 51- 60 years age group & 72% were male and 28% were female patients. In this series 24% were illiterate. Of the literate group 39% went to primary school, 20% completed SSC, 8% completed HSC, 5% completed graduation and only 4% completed post-graduation. Majority of the patients were unemployed (22%). Other was businessman (20%), housewife (19%) and cultivator (16%). 63% percentage of the patients from low income group, which was followed by middle income group (33%). Majority 53% patients had Ischaemic stroke, 45% Intracerebral haemorrhage (ICH) and only 2% had Subarachnoid haemorrhage (SAH). 77% of patient had history of hypertension, 22% Diabetes mellitus, 20% Dyslipidaemia, 13% Previous Stroke, 27% Ischaemic heart disease. Out of 77 hypertensive stroke patients 37(48.05%) had haemorrhagic stroke & 40(51.94%) had ischemic stroke. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 18-22 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16920